Analysis and countermeasures of the exchange difficulty of Chinese rhythmic gymnastics group exercises during the Tokyo Olympic cycle - Li, N.; Huang, J.-Y. (Journal of Beijing Sport University, 2020)
In order to enhance the exchange difficulty level of Chinese Rhythmic gymnastics group exercises, win the qualification of 2020 Tokyo games successfully and achieve excellent results, using the methods of documentation, video analysis and mathematical statistics, the paper analyzes the differences of exchange difficulties in five hoops, three balls and two ropes between the Top 8 and the Chinese Team of the group exercises all-around performance at the 36 th Rhythmic Gymnastics World Championships in 2018, explores the deficiency of the exchange difficulty of Chinese Rhythmic Gymnastics group exercises and puts forward feasible countermeasures. Conclusions: The exchange difficulty score has a significant impact on the total score of the performance score; compared with the 5 hoops, the 3 balls and 2 ropes exchange difficulty scores have greater influence on the total score; there is a significant difference in the exchange difficulty score between 5 hoops and 3 balls and 2 ropes; six meters, body difficulty, outside the visual field and without the help of the hands are more often used in exchange difficulty additional criteria; catch of the ball with one hand and passing through the rope are less used. Lower difficulty points and poorer execution quality as well as insufficient artistic composition are the problems of exchange difficulty in Chinese Rhythmic Gymnastics group exercises. The countermeasures are to deeply interpret the code of points and accurately grasp the code of points` orientation, strive to improve the exchange difficulty score and ensure the execution quality of the exchange difficulty, make reasonable arrangements and ingenious designs, attach great importance to contingency plans and properly deal with the risks on the field.